Initial Experience with Single-Agent Docetaxel as Neoadjuvant Therapy in Men with Locally Advanced Prostate Cancer - Klein, Eric A (MedReviews, LLC, 2003)
Patients with locally advanced prostate cancer have worse outcomes after radical prostatectomy (RP) than patients with more favorable parameters. The findings of large, contemporary, RP series have led investigators at a number of centers to evaluate the potential role of neoadjuvant chemotherapy in patients with locally advanced disease. A currently ongoing study of 28 patients explores the antitumor response of a regimen of single-agent, docetaxel, 40 mg/m(2), administered intravenously on a weekly schedule for 6 weeks to patients with locally advanced prostate cancer before RP. Docetaxel has demonstrated significant antitumor activity in patients with advanced, androgen-independent disease. Study results showed that 75% of patients had reductions in prostate-specific antigen (PSA) levels ranging from 9%–79% at the completion of docetaxel therapy. In 25% of the patients, PSA levels increased by 2%–18% from baseline to completion of chemotherapy. In addition, noncastrate levels of testosterone were maintained in all patients. The docetaxel therapy has also been relatively well tolerated. Reporting of the primary endpoint of pathologic response is pending completion of accrual and surgery.